2017
DOI: 10.13064/ksss.2017.9.1.019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pause in English speaking evaluation

Abstract: The main objective of this study is to investigate the influence of utterance internal pause in English speaking evaluation. To avoid possible confusion with other errors caused by segmental and prosodic inaccuracy, stem utterances with two different length obtained from a native speaker were manipulated to make a set of stimuli tokens through insertion of pauses whose length and position vary. After a total of 90 participants classified into three proficiency groups rated the stimuli, the scored data set was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This study also suggests pitch contour lines regarding intonational characteristics such as declination and boundary tones contribute to proficiency judgment. The advanced group could be distinguished from low-level group through the number of inserted pauses, as many other studies have suggested (Bosker et al, 2013;Kang et al, 2010;Kim, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…This study also suggests pitch contour lines regarding intonational characteristics such as declination and boundary tones contribute to proficiency judgment. The advanced group could be distinguished from low-level group through the number of inserted pauses, as many other studies have suggested (Bosker et al, 2013;Kang et al, 2010;Kim, 2017).…”
Section: Discussionmentioning
confidence: 89%